2021
DOI: 10.5194/hess-25-6087-2021
|View full text |Cite
|
Sign up to set email alerts
|

Response of water fluxes and biomass production to climate change in permanent grassland soil ecosystems

Abstract: Abstract. Effects of climate change on the ecosystem productivity and water fluxes have been studied in various types of experiments. However, it is still largely unknown whether and how the experimental approach itself affects the results of such studies. We employed two contrasting experimental approaches, using high-precision weighable monolithic lysimeters, over a period of 4 years to identify and compare the responses of water fluxes and aboveground biomass to climate change in permanent grassland. The fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…This suggests that warming can cause a shift from energy‐limited to water‐limited conditions in such montane grasslands. As shown by Forstner et al (2021) shifts from energy‐limited to water‐limited conditions affected not only the soil water storage but also evapotranspiration and seepage. This complicates the assessment of drought impacts, because the impact of precipitation deficits on the individual components of the soil water budget depends on a variety of factors.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This suggests that warming can cause a shift from energy‐limited to water‐limited conditions in such montane grasslands. As shown by Forstner et al (2021) shifts from energy‐limited to water‐limited conditions affected not only the soil water storage but also evapotranspiration and seepage. This complicates the assessment of drought impacts, because the impact of precipitation deficits on the individual components of the soil water budget depends on a variety of factors.…”
Section: Discussionmentioning
confidence: 88%
“…The lysimeter weight and the seepage weight provide information about the soil water balance components precipitation ( P ), actual evapotranspiration ( ET a ) and seepage rate ( NetQ ), that is, the water flux across the lysimeter bottom. To quantify P , ET a and NetQ , data processing with manual and technical correction was necessary to compensate disturbances due to external forces on the lysimeter such as wind, manual operations (cutting events, maintenance) or animals (Forstner et al, 2021). The changes in soil water storage (Δ S ) obtained from the lysimeter water budget (Equation ) were used to determine the amount of available moisture within a plant's root zone: italicΔSgoodbreak=Pgoodbreak−ETagoodbreak−italicNetQ. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the space-for-time substitution approach, one possibility to deal with a limited site-specific range of observations for model calibration could be to use data from manipulative experiments to broaden the training dataset for model calibration. For example, Forstner et al (2021) showed that only the combined use of observational and manipulative climate change experiments was able to identify how altering individual and multiple drivers (i.e., reduced R, elevated CO 2 , and surface temperatures, increase in ET 0 ) affect ecosystem functioning of grassland ecosystems on changing climate conditions. Still, many challenges remain in addition to those discussed above, such as consideration of changes in soil properties due to climatic changes and the effects of these changes on model parameters or hints on missing model structures, depending on changing climatic conditions (e.g., Robinson et al, 2016Robinson et al, , 2019.…”
Section: Modeling Crop-soil-ecosystem Response To Changing Boundary C...mentioning
confidence: 99%
“…This indicates a possibly small impact of NREs on the results of this study. However, NRE (i.e., dew, hoar frost and fog) can contribute a substantial amount of water for the ecosystem at the annual scale (Forstner et al, 2021;Groh et al, 2019), which demonstrates clearly that high-precision lysimeters are ideal tools measuring the different NRE of ecosystems. A higher temporal resolution of the data, possibly 10-min intervals, could help to temporally delineate precipitation events and NRE, as used by Groh et al (2018b).…”
Section: Lysimeter Measurements Reference Values and The Influence Of...mentioning
confidence: 99%